The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1073/pnas.1702943114
|View full text |Cite
|
Sign up to set email alerts
|

Maternal photoperiod programs hypothalamic thyroid status via the fetal pituitary gland

Abstract: In wild mammals, offspring development must anticipate forthcoming metabolic demands and opportunities. Within species, different developmental strategies may be used, dependent on when in the year conception takes place. This phenotypic flexibility is initiated before birth and is linked to the pattern of day length (photoperiod) exposure experienced by the mother during pregnancy. This programming depends on transplacental communication via the pineal hormone melatonin. Here, we show that, in the Siberian ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 47 publications
(56 reference statements)
6
54
0
Order By: Relevance
“…Functional studies show that the developmental trajectory set by the prenatal photoperiodic experience continues in juveniles pinealectomised or reared in constant light, and thus in the absence of postnatal melatonin . In our recent study, we observed that juvenile Siberian hamsters gestated in either LP (16 h L day ‐1 ) or SP (8 h L day ‐1 ) and transferred to IP (14 h L day ‐1 ) at weaning (Figure A) presented melatonin peaks of similar duration, regardless of their experience (Figure B), as observed previously . These results suggest that MPP does not arise from altered circulating melatonin patterns in juveniles, although it may result from a change in their sensitivity to melatonin signalling.…”
Section: Maternal Photoperiodic Programming: Primed By Maternal Melatsupporting
confidence: 86%
See 4 more Smart Citations
“…Functional studies show that the developmental trajectory set by the prenatal photoperiodic experience continues in juveniles pinealectomised or reared in constant light, and thus in the absence of postnatal melatonin . In our recent study, we observed that juvenile Siberian hamsters gestated in either LP (16 h L day ‐1 ) or SP (8 h L day ‐1 ) and transferred to IP (14 h L day ‐1 ) at weaning (Figure A) presented melatonin peaks of similar duration, regardless of their experience (Figure B), as observed previously . These results suggest that MPP does not arise from altered circulating melatonin patterns in juveniles, although it may result from a change in their sensitivity to melatonin signalling.…”
Section: Maternal Photoperiodic Programming: Primed By Maternal Melatsupporting
confidence: 86%
“…increasing doses of TSH previously shown to cause minimal effects on dio2 expression . Accordingly, 0.5 mIU of TSH induced dio2 mRNA expression in both LP‐IP and SP‐IP animals, whereas 1 mIU of TSH further increased dio2 mRNA expression in SP‐IP animals, although not in the LP‐IP group, demonstrating a decreased sensitivity to TSH in LP‐IP animals, which is an effect that was not associated with changes in TSH‐r mRNA expression, nor circulating TH feedback on deiodinase expression . This change in the level of dio2 expression to a given TSH mRNA level was recently reported in a study exploring critical photoperiods in sheep .…”
Section: Maternal Photoperiodic Programming Occurs In Tanycytesmentioning
confidence: 70%
See 3 more Smart Citations